Mask-wearing affects infants' selective attention to familiar and unfamiliar audiovisual speech - Slivka, Lauren N.; Clayton, Kenna R. H.; Reynolds, Greg D. (Frontiers in Developmental Psychology, 2025)
This study examined the immediate effects of mask-wearing on infant selective visual attention to audiovisual speech in familiar and unfamiliar languages. Infants distribute their selective attention to regions of a speaker's face differentially based on their age and language experience. However, the potential impact wearing a face mask may have on infants' selective attention to audiovisual speech has not been systematically studied. We utilized eye tracking to examine the proportion of infant looking time to the eyes and mouth of a masked or unmasked actress speaking in a familiar or unfamiliar language. Six-month-old and 12-month-old infants (n = 42, 55% female, 91% White Non-Hispanic/Latino) were shown videos of an actress speaking in a familiar language (English) with and without a mask on, as well as videos of the same actress speaking in an unfamiliar language (German) with and without a mask. Overall, infants spent more time looking at the unmasked presentations compared to the masked presentations. Regardless of language familiarity or age, infants spent more time looking at the mouth area of an unmasked speaker and they spent more time looking at the eyes of a masked speaker. These findings indicate mask-wearing has immediate effects on the distribution of infant selective attention to different areas of the face of a speaker during audiovisual speech.